2019
DOI: 10.1097/pcc.0000000000001968
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Asphyxia Arrest Duration on a Pediatric End-Tidal co 2-Guided Chest Compression Delivery Model*

Abstract: Objective: To determine the effect of the duration of asphyxial arrest on the survival benefit previously seen with end-tidal carbon dioxide (ETCO 2 )-guided chest compression delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 57 publications
0
17
0
Order By: Relevance
“…We also found an effect of asphyxia duration on the use of ETCO 2 ‐guided CPR. We found that, like our 20‐minute arrest study, after a 17‐minute asphyxia and fibrillation arrest the rate of ROSC was higher in the ETCO 2 ‐guided CPR group than in the standard CPR group (64% vs 21%, P = .05) but, after a 23‐minute arrest, ETCO 2 ‐guided CPR was as ineffective as standard CPR (7% vs 21%) . We use an asphyxial cardiac arrest model because respiratory insufficiency is one of the most common causes of pediatric cardiac arrest, including arrest in the operating room .…”
Section: Introductionmentioning
confidence: 62%
See 4 more Smart Citations
“…We also found an effect of asphyxia duration on the use of ETCO 2 ‐guided CPR. We found that, like our 20‐minute arrest study, after a 17‐minute asphyxia and fibrillation arrest the rate of ROSC was higher in the ETCO 2 ‐guided CPR group than in the standard CPR group (64% vs 21%, P = .05) but, after a 23‐minute arrest, ETCO 2 ‐guided CPR was as ineffective as standard CPR (7% vs 21%) . We use an asphyxial cardiac arrest model because respiratory insufficiency is one of the most common causes of pediatric cardiac arrest, including arrest in the operating room .…”
Section: Introductionmentioning
confidence: 62%
“…We conducted a retrospective, secondary analysis of data from piglet cardiac arrest studies that we published previously as well as unpublished studies. All studies were approved by the Animal Care and Use Committee at the Johns Hopkins University.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations